PREFERENSI WISATAWAN TIMUR TENGAH TERHADAP PRODUK WISATA DI KABUPATEN BADUNG - Rahayu Wulan Dewi, Ni Komang; Sasrawan Mananda, I Gusti Putu Bagus; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p16, 2021)
This study aims to find preferences of Middle Eastern tourists towards tourism products of Badung Regency and involved 100 purposively selected respondents. The data was collected through questionnaires then processed using crosstab analysis method and chi-square test. The results of this study are: 1) Characteristics of Middle Eastern tourists visiting Badung Regency are dominated by women, aged between 25 – 44 years, private employees, married, nationality of Saudi Arabia, Turkey and Egypt, purpose of visit for vacation, information about Bali from internet, mostly traveled by tour packages, length of stay between 4 - 6 days, and mostly it’s their first time visit to Bali. 2) Preferences as follows prefer for natural attractions, stay in Kuta/Legian area, prefer to use a car rental, reserved resort as their accommodation through booking services, dining at restaurants, a watersport as entertainment activities, online media as information services, tourism consulting services are Bali tourism research, do not use tourist flights, and do massages when traveling to Bali. The characteristics of Middle Eastern tourists that correlate with the preference of selection of tourist products in Badung Regency is; Age correlates with tourism consulting services. Jobs correlate with tourist transport services. Nationality correlates with tourism transportation services, travel services, accommodation provision, tourism consulting services, travel services, tirta tours, and spas. Resources correlate with tourist transportation services, and the provision of accommodation. Travel organizing correlates with tourist transportation services, travel services, food and beverage services, and travel services. Travel periods correlate with tourist attractions, and tourism consulting services. Periodic travel correlates with travel services.